EXPRESSION THE CONCEPT OF PAIN IN PATIENTS WITH SICKLE CELL ANEMIA (A QUALITATIVE STUDY): Life Sciences-Medical - HOSSEINI NIK AMMAR; ABDEYAZDAN GHOLAM HOSSEIN; D.R HEIDAR ALI ABEDI (International Journal of Life Science and Pharma Research, 2022)
Sickle Cell Anemia is the commonest inherited disease in world which is caused by a mutation in genes that leads to abnormal hemoglobin and defectivered blood cells. Red blood cells become rigid and sticky and deforms into sickles or crescent moons which are unable to move in vessels. They, therefore, block blood flow, decrease tissue oxygen, and finally lead to ischemia. Each year 300 thousand infants are born with SCD. 300 million people in world and 2.5 million in the U.S. are affected with SCD. The disease has several symptoms and signs. Periodic episodes of pain, called crises, are a major symptom of sickle cell anemia. The recurrence of pain is completely unpredictable. This study aims to investigate the pain experience in patients with SCD. Considering the nature of the study a philosophical research method, descriptive phenomenology, was used. Participants consisted of 11 patients (4 females and 7 males) with Sickle Cell Disease in Kohkiloye-Boyerahmad Province, Iran. Sampling was done on the basis of the aim of the study. Interviews were unstructured and a 7-stage Colaizzi Method was used to analyze and codify the collected data. 100% of participants complained of pain and described it as its worst experience. 40 first-level codes and 3 second-level codes were extracted including the cause of pain recurrence, pain consequences, and the type of pain which altogether created the main concept of pain. Participants complain about irregular severe pains which disturb their normal life. It is suggested their needs and problems be addressed specifically. Particular programs are required to support these patients, meet their needs, and improve the quality of their lives.